Laser‐Induced Phase Transition and Patterning of hBN‐Encapsulated MoTe2 (Small 17/2023). Issue 17 (27th April 2023) - Ryu, Huije; Lee, Yunah; Jeong, Jae Hwan; Lee, Yangjin; Cheon, Yeryun; Watanabe, Kenji; Taniguchi, Takashi; Kim, Kwanpyo; Cheong, Hyeonsik; Lee, Chul‐Ho; Lee, Gwan‐Hyoung
Abstract : hBN‐Encapsulated MoTe2 In article number 2205224, Gwan‐Hyoung Lee and co‐workers investigate phase transition in a laser‐irradiated MoTe2 with various stacked geometries. Depending on the passivation and temperature of the laser‐irradiated sample, 2H‐MoTe2 transforms into various phases, such as Td, 1T′, Mo3 Te4, and Te. In the hBN‐encapsulated MoTe2, 2H‐1T′ heterophase can be patterned by local laser‐irradiation, leading to a low contact resistivity of 1.13 kΩ μm.